Surface roughness of FIB sputtered silicon - Ali, Mohammad Yeakub; Hung, N. P.; Yuan, S. (Kluwer Academic Publishers (Springer), 2001)
Mathematical models are developed to calculate the surface roughness of focused-ion-beam (FIB) sputtered surface. The surface roughness is the combination of the beam function and the material function. The beam function includes ion type, acceleration voltage, ion flux, intensity distribution, dwell time, etc; the material function includes the inherent material properties related to FIB micromachining. Surface of FIB sputtered (100) silicon was characterized using atomic force microscope. Reasonable agreement between the calculated and measured surface roughness was found.